Surveillance-based estimation of the malaria disease burden in a low endemic state of Punjab, India, targeted for malaria elimination. (4th February 2021) - Kaur, Jaspreet; Kaura, Taruna; Sharma, Ayush; Kumar, Ashish; Pangotra, M K; Upadhyay, A K; Anvikar, Anupkumar; Grover, Gagandeep S; Chaturvedi, H K; Sharma, Surya K
Abstract: Background: The state of Punjab in India qualifies for malaria elimination because the number of cases reported through routine surveillance is in decline. However, surveillance system prevalence mainly provides malaria trends. Therefore, a prospective epidemiological study was designed to estimate the malaria burden in the state. Methods: District-wise annual parasite incidence (API) was used for identification of three strata, representing high, moderate and low API zones. A total of 0.9 million people from nine districts was under malaria surveillance for 1 y. The weighted estimates of API for the three regions was calculated and combined to give an estimate of API for the total population of the state. Results: Based upon the primary data generated, malaria cases from high, moderate and low malaria-endemic areas were estimated to be 3727, 904 and 106, respectively. Further, the total number of malaria cases in the state was estimated to be 4737 (95% CI 4006 to 5469) cases per annum. Conclusion: Actual burden of malaria in the state of Punjab, India, is about seven to eight times higher than that reported by routine surveillance activities. However, the state still qualifies for malaria elimination but needs vigorous efforts to strengthen the active surveillance and reporting system along with implementation of effective control strategies to achieve malaria elimination.